Converting gambling to philanthropy and acts of patriotism: The case of "The world's most Swedish gambling company". (April 2020) - Kroon, Åsa
Highlights: Moderate gambling ads may contain problematic ideological content. Gambling ads may use highly nationalistic and patriotic discourse. Gambling ads convert gambling practices to philanthropy and conceal risks. More research should be conducted on gambling ads in their socio-cultural contexts. Abstract: This paper presents a case study of a contemporary Swedish gambling ad video from Svenska Spel published on YouTube. The study applies critical multimodal analysis to examine with what communicative strategies the state-owned operator positions itself on the soon-to-be de-regulated Swedish gambling market. The focus in the analysis lies on the linguistic and visual choices used to achieve certain communicative goals in relation to the consumer. The results show that nationalistic and patriotic values are conveyed and used in order to connect to an implied male consumer who is both 'Swedish' and of multi-ethnic origin; the latter being positioned as an Other in need of being taught about the Swedish values of fairness, trustworthiness and authenticity. Deleted from the advertisement is anything having to do with gambling as a social practice. Svenska Spel's identity is visually and linguistically converted from that of a gambling company into a philanthropist whose business quite unproblematically gain society and its "Swedish" people. The study raises questions regarding demands for "moderate" gambling advertisements, and suggests that current moderation regulations miss the mark when it comes to identifying and regulating problematic ideological content in seemingly inconspicuously designed gambling advertising.